Neospora caninum and Leishmania infantum Co-Infection in Domestic Dogs (Canis familiaris) in Meshkin-Shahr District, Northwestern Iran - M Sharifdini; M Mohebali; H Keshavarz; M Hosseininejad; H Hajjaran; B Akhoundi; A Rahimi Foroushani; Z Zarei; S Charehdar (Tehran University of Medical Sciences, 2011)
Background: Mediterranean visceral leishmaniasis (MVL)is an infectious disease that affects both human and animals. Domestic dogs (Canis familiaris) are principal reservoir hosts of MVL caused by Leishmania infantum. Dogs are definitive hosts for Neospora caninumand a risk factor for infecting intermediate hosts. The immunosuppression caused by visceral leishmaniasis (VL) can promote the occurrence of co-infections with other agents such as neosporosis. This study aimed to determine the frequency of co-infection of the both protozoan parasites in the endemic areas of VL from Meshkin-Shahr District, north-west of Iran. Methods: Altogether, 171 serum samples were collected from domestic dogs of Meshkin- Shahr District by multistage cluster sampling from October 2008 to August 2009. The collected serum samples were tested for the detection of simultaneous infection of L. infantum and N. caninum using direct agglutination test (DAT) and indirect ELISA, respectively. Results: Of the 171 domestic dogs, 27 (15.8%) and 52 (30.4%) were showed antibodies against L. infantum and N. caninum, respectively. Simultaneous infections of N. caninum and L. infantum was found in 16 (9.4%) of the dogs. In VL-positive and VL-negative dogs, N. caninum infection was found in 59.3% and 25.0%, respectively. A statistically significant difference was found between VL-positive and VL-negative dogs with N. caninum infection (P= 0.001). Conclusion: These findings indicate that Meshkin-Shahr District in northwestern Iran is an active focus of canine visceral leishmaniasis (CVL). Neospora caninum and L. infantum co-infection is prevalent in the area and infection by L. infantum seems to enhance susceptibility to N. caninum infection in domestic dogs.